The feasibility and safety of eustachian tube dilation with a standard endovascular balloon: a clinical pilot study - Valerie Dahm; Justin T. Lui; Soyeon Jung; Vincent Y. Lin; Joseph M. Chen; Trung N. Le (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Obstructive eustachian tube dysfunction is a common pathology, generally accepted as the underlying cause for chronic ear diseases. Eustachian tube dilation has shown promising results in randomized controlled trials, but is a costly procedure. The aim of the current study was to assess the feasibility of transnasal balloon dilatation of the eustachian tube with an endovascular balloon in the context of ease of use, maneuverability, and safety. Methods Clinical pilot study carried out at a university tertiary care facility. In total, twelve patients, were included over a period of 6 months. All patients underwent tympanoplasty or tympanomastoidectomy surgeries. Eustachian tube dilation was carried out transnasal using an endovascular balloon. A computed tomography was carried out after surgery to assess for any potential damages and compared to preoperative imaging studies. Postoperative endoscopy was performed intraoperatively and at follow up to assess for any potential damages. Results All eustachian tube dilations were carried out successfully. No severe adverse events were noted during the procedure, in the postoperative period, or on imaging studies. Minor adverse events such as mild intraoperative bleeding was managed in a routine fashion. Conclusions Balloon dilation of the eustachian tube with the endovascular balloon was feasible and safe in all cases. It is likely a more cost-effective alternative to commercially available balloons with similar designs and specifications. Trial registration The study was registered at clinicaltrials.gov; NCT04809753, initial release February 24th, 2021. Graphical Abstract